Relationships between the parameters of uric acid exchange and electroencephalograms in humans - Igor Bombushkar; Igor Popovych; Walery Zukow (Kazimierz Wielki University, 2023)
Background. During the implementation of the project "Physiological activity of uric acid", our group discovered four variants of the combination of levels of uricemia and uricosuria both in healthy rats and in people with chronic pyelonephritis and cholecystitis in the remission phase, which are accompanied by characteristic constellations of parameters of the autonomic nervous, endocrine, and immune systems, as well as the exchange of nitrogenous metabolites and electrolytes, the levels of which correlate with uricemia and/or uricosuria. The aim of this study is to clarify the relationship between parameters of uric acid metabolism and electroencephalogram (EEG) in humans. Materials and methods. Under an observations were 34 males and 10 females by age 24-76 years with chronic pyelonephritis and cholecystitis in the phase of remission. The object of the study was serum and urine levels of uric acid (uricase method) as well as EEG. Results. It was identified 12 parameters as characteristic of uric acid metabolism clusters. Another 42 EEG parameters were found to be out of the discriminant model, despite the clear recognition ability. A strong canonical correlation between EEG parameters and uricemia (R=0,729) and a moderate correlation with uricosuria (R=0,553) were revealed. Even stronger connections were found between changes in parameters of uric acid metabolism and EEG under the influence of balneotherapy: R=0,901 and 0,681 respectively. Conclusion. Uric acid has both activating and inhibitory effects on EEG parameters. The neurotropic effect of uric acid as a structural analogue of methylxanthines and adenosine is realized, apparently, through various adenosine receptors.